Global Perspectives on Non-Governmental Organizations - Bobek, Vito; Horvat, Tatjana (IntechOpen, 2023)
This book provides a comprehensive overview of non-governmental organizations (NGOs), including their development, structure, marketing, and challenges. It is divided into two sections: "Management Aspects of NGOs in the Area of Development, Marketing and Sourcing", and "Case Studies of NGOs". Chapters discuss the development of NGOs and present case studies of NGOs in various countries, including Ethiopia, Bangladesh, South Africa, and others. They also address such topics as NGOs in the healthcare sector, the effect of the COVID-19 pandemic on the humanitarian supply chain, and how NGOs can protect and preserve cultural heritage.